2017
DOI: 10.1055/s-0043-106184
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of abnormalities in small-bowel diseases using probe-based confocal laser endomicroscopy

Abstract: Background and study aims  Probe-based confocal laser endomicroscopy (pCLE) enables real-time optical biopsy. Little is known about pCLE imaging deep inside the small bowel, therefore the aim of this study was to determine its usefulness. Patients and methods  Between April 2014 and January 2016, we performed 38 pCLE examinations during double-balloon enteroscopy with intravenous fluorescein in 37 patients with: tumors (n = 10), vascular disorders (n = 6), inflammatory diseases and drug injuries (n = 13), othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The present study showed that dark pleomorphic nests and disorganized irregular‐shaped dark glands were observed in patients with rectal metastasis from lung adenocarcinoma and SEL‐like extremely well‐differentiated gastric adenocarcinoma, respectively. We also reported that probe‐based CLE showed irregular dark nests in jejunal metastasis from cervical cancer, disorganized irregular dark glands in early‐stage gastric cancer covered by nontumorous regenerative epithelium or maturated atypical glands found after Helicobacter pylori eradication, and back‐to‐back orientation of dark crypts in ulcerative colitis‐associated differentiated adenocarcinoma and dark trabecular architecture in ulcerative colitis‐associated undifferentiated adenocarcinoma . The Miami classification system based on a consensus of probe‐based CLE users to standardize categorization of images indicated that all cancers in the esophagus, stomach, colorectum, and biliary duct were characterized by disorganized structures of dark (“nonrefractile”) epithelium or cells .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The present study showed that dark pleomorphic nests and disorganized irregular‐shaped dark glands were observed in patients with rectal metastasis from lung adenocarcinoma and SEL‐like extremely well‐differentiated gastric adenocarcinoma, respectively. We also reported that probe‐based CLE showed irregular dark nests in jejunal metastasis from cervical cancer, disorganized irregular dark glands in early‐stage gastric cancer covered by nontumorous regenerative epithelium or maturated atypical glands found after Helicobacter pylori eradication, and back‐to‐back orientation of dark crypts in ulcerative colitis‐associated differentiated adenocarcinoma and dark trabecular architecture in ulcerative colitis‐associated undifferentiated adenocarcinoma . The Miami classification system based on a consensus of probe‐based CLE users to standardize categorization of images indicated that all cancers in the esophagus, stomach, colorectum, and biliary duct were characterized by disorganized structures of dark (“nonrefractile”) epithelium or cells .…”
Section: Discussionmentioning
confidence: 85%
“…nCLE examinations were carried out between 40 s and 20 min after i.v. injection of 250 mg fluorescein (100 mg/mL, Fluorescite; Novartis Pharma K.K., Tokyo, Japan) as described previously . For EUS‐FNA, the needle was moved back and forth 20 times within the lesion keeping away from necrosis, if any, while suction was applied using a 20‐mL syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 38 pCLE examinations performed during a double-balloon enteroscopy, identified characteristic pCLE features of various small-bowel diseases based on the size of the capillary calibres and lymphatic vessels. CLE pathological features correctly correlated with histopathologic diagnosis in 91% cases (31).…”
Section: Small Bowelmentioning
confidence: 81%
“…The pCLE benefits patients who are taking antithrombotic agents, who have bleeding tendencies, or who have a condition for which taking pathologic samples is contraindicated or not recommended. 2 Even if regenerating nontumorous epithelium overlies the tumorous tissue, pCLE may be able to detect it by visualization of the subsurface microscopic architecture less than 100 μm in depth. 3 In conclusion, pCLE could help in the in vivo diagnosis of submucosal hypervascular tumors such as GIST in cases in which biopsy is not recommended.…”
mentioning
confidence: 99%